Azerbaijan-Italy Relations: Legal Foundations, Bilateral Agreements, and Multilateral Dynamics - Baba-zade, Rafi (My University, 2026)
The relationship between Azerbaijan and Italy is dynamic and multifaceted, founded on shared strategic interests, including energy, legal cooperation, and regional diplomacy. However, diplomatic relations were formalized in 1992, on Azerbaijan’s independence from the Soviet Union; the roots of this relationship date back to the early twentieth century. As part of Azerbaijan's brief independence as the Azerbaijan Democratic Republic (ADR) from 1918 to 1920, Italy closely monitored the events in the South Caucasus, as Azerbaijan possessed oil and a strategic geopolitical position. Italy did not officially accept the ADR, but did not legalize the Soviet annexation of Azerbaijan, which was consistent with the later UN General Assembly Resolution 2625 (1970), which condemned territorial acquisition through force1 . This partnership has grown from energy trade to judicial modernization, climate law, investment protection, and digital governance over the last three decades. Azerbaijan’s role in European energy diversification has been reinforced with the completion of the Trans-Adriatic Pipeline (TAP), which has been operational since 2020.2 This development has been enhanced by political trust, based on Italy’s consistent support for Azerbaijan’s territorial integrity regarding the Nagorno-Karabakh conflict, as well as societal ties strengthened through cultural diplomacy and educational exchanges. This thesis examines the factors influencing the relations between Azerbaijan and Italy through laws that seek to achieve the same goal without EU membership or formal alignment. The analysis focuses on the possibilities of using the 1997 Bilateral Investment Treaty and the 2004 Double Taxation Avoidance Agreement, as well as cooperation within the NATO Partnership for Peace and the EU’s Eastern Partnership, as a legal framework for energy, procurement, and climate policy, which would make EU oversight unnecessary.
Keywords: Azerbaijan -- Foreign relations -- Italy.; Azerbaijan -- Foreign relations -- 1918-1920.; International relations -- Legal aspects.; Italy -- Foreign relations.